POLITIK HUKUM PEMBATASAN MASA JABATAN PRESIDEN - Zulhidayat, Muhammad; Risfani, Melly (Riau Law Journal, 2023)
AbstractThis research is conducted by discussing in a legal perspective the discourse that will be carried out by increasing the term of office of the president. Although this did not happen, if this discourse continues to be developed in the future it will have a negative effect on leadership in Indonesia. This can be seen from the legal facts that occurred during the New Order era, the President led 32 years so that it had a bad influence on the government. This research utilizes a normative legal approach to clarify the research conducted. All sources are adjusted to secondary sources that have been published through various sources. The conclusions in this study are, first, the extension of the presidential term in the view of the law is not allowed because it will violate the provisions of the state constitution that have been strengthened in the 1945 Constitution. For this reason, from a legal perspective, this extension means that there is a contradiction in the constitution and violates the Indonesian constitution. Secondly, if we make a comparison with the United States, then there the President's term of office is limited to 2 periods, with 1 period of only 4 years. The lesson from many countries is that if a ruler is in power for too long, the enthusiasm to run the government is exhausted, but the lust for power remains great. AbstrakPenelitian ini dilakukan dengan membahas secara perspektif hukum mengenai wacana yang akan dilakukan dengan menambah masa jabatan dari presiden. Walaupun hal ini tidak terjadi, apabila wacana ini terus dikembangkan kedepannya akan berpengaruh buruk pada kepemimpinan di Indonesia. Hal ini bisa dilihat dari fakta hukum yang terjadi pada masa orde baru, presiden memimpin 32 tahun sehingga membawa pengaruh buruk dalam pemerintahan. Penelitian ini memanfaatkan pendekatan hukum normatif untuk memperjelas penelitian yang dilakukan. Semua sumber disesuaikan dengan sumber sekunder yang sudah dipublikasikan melalui berbagai sumber. Kesimpulan dalam penelitian ini adalah pertama, perpanjangan masa jabatan presiden tidak diperbolehkan karena akan melanggar ketentuan konstitusi negara. Kedua, jika kita membuat suatu perbandingan dengan Amerika Serikat, maka di sana masa jabatan presiden dibatasi 2 periode, dengan 1 periode hanya 4 tahun saja, Jika seorang penguasa terlalu lama berkuasa, semangat untuk menjalankan pemerintahan sudah habis, tapi nafsu untuk berkuasa tetap besar.